2021
DOI: 10.3892/ol.2021.12931
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing of BCL‑X and implications for treating hematological malignancies (Review)

Abstract: BCL-X is a member of the BCL-2 family. It regulates apoptosis and plays a critical role in hematological malignancies. It is well-known that >90% of human genes undergo alternative splicing. A total of 10 distinct splicing transcripts of the BCL-X gene have been identified, including transcript variants 1-9 and ABALON. Different transcripts from the same gene have different functions. The present review discusses the progress in understanding the different alternative splicing transcripts of BCL-X, including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Studies to date have shown that the BCL-x gene, a member of the BCL-2 family, enables different transcripts from the same gene to have the same or different expression patterns and functions through alternative splicing. 16 Therefore, we selected all transcripts and the transcript NR 134251.1 of APTR in this study to research its function and mechanism. 16HBE cells were treated with different concentrations of sodium arsenite for 48 h, and the expression of all transcripts and the transcript NR 134251.1 of lncRNA APTR showed a dose-dependent promotion.…”
Section: Discussionmentioning
confidence: 99%
“…Studies to date have shown that the BCL-x gene, a member of the BCL-2 family, enables different transcripts from the same gene to have the same or different expression patterns and functions through alternative splicing. 16 Therefore, we selected all transcripts and the transcript NR 134251.1 of APTR in this study to research its function and mechanism. 16HBE cells were treated with different concentrations of sodium arsenite for 48 h, and the expression of all transcripts and the transcript NR 134251.1 of lncRNA APTR showed a dose-dependent promotion.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the alternative isoform of CD44, which is extensively studied across various cancer types, is linked to the epithelial-to-mesenchymal transition ( 31 ). The utilization of alternative 5′ splice sites in Bcl-x pre-mRNA results in the formation of the anti-apoptotic Bcl-x(L) and pro-apoptotic Bcl-x(S) protein isoforms ( 32 , 33 ). Bcl-x(L) is transcriptionally upregulated in numerous cancers and is linked to chemoresistance, as well as to the RAS-induced expression of stemness regulators and the preservation of a cancer-initiating cell phenotype ( 34 ).…”
Section: Concise View Of the Alternative Splicing In Cancermentioning
confidence: 99%
“…Hence, depending on the balance between Bcl-xL and Bcl-xS, BCL-x can either be pro- or anti-apoptotic. As such, the balance between these two antagonistic isoforms is tightly regulated and overexpression of the anti-apoptotic Bcl-xL isoform has been linked to resistance to chemotherapy in several cancers ( 12 , 13 ), whereas overexpression of the pro-apoptotic Bcl-xS isoform is associated to some forms of diabetes and cardiac disorders ( 14 , 15 ). Therefore, pharmacological means to switch the splicing in favour of Bcl-xS may have therapeutic benefits for a number of cancers, in particular those resistant to chemotherapy due to Bcl-xL overexpression.…”
Section: Introductionmentioning
confidence: 99%